Investigating the mechanism by which the platelet-derived growth factor receptor promotes metastasis in medulloblastoma - AbouAntoun, Thamara Jihad (2008)
Expression of the platelet-derived growth factor receptor (PDGFR) correlates with metastatic medulloblastoma and PDGF treatment of medulloblastoma cells activates the pro-survival and pro-migratory pathways downstream of the receptor, for instance, increases extra-cellular regulated kinase (Erk1/2), Protein kinase B (Akt) and phosphatidylinositide 3-kinase (PI3K) activity and decreases phosphatase and tensin homolog (PTEN) expression and activity. PDGFR can also heterodimerize with and transactivate the epidermal growth factor receptor (EGFR). Our overarching hypothesis was to determine whether targeting PDGFR activity effectively inhibits signaling required for medulloblastoma cell migration and invasion and whether it blocks PDGFR-induced transactivation of EGFR. To explore this we used Daoy and D556 human medulloblastoma cells which we transfected with small interfering RNA (siRNA) to PDGFRβ or treated with either Imatinib mesylate (Gleevec®) or Sunitib Malate (SUTENT®), specific inhibitors of PDGFR, to block PDGFR expression and activity, respectively. Cell migration, survival and PDGFR signaling following PDGF-BB stimulation of serum-depleted cells, with and without PDGFR inhibition, was measured. PDGF-BB treatment of cells enhanced migration and proliferation after 24 hr; increased PDGFRβ, PI3K, Akt and Erk1/2 activity, decreased PTEN activation and transactivated EGFR. Imatinib (1 uM) treatment of PDGFRβ active cells induced apoptosis at 72 hr and inhibited migration at 24 hr and invasion at 48 hr after a single dose and concomitantly inhibited PDGF-BB activation of PDGFRβ, PI3K, Akt and Erk1/2 but promoted PTEN activity. SUTENT (0.2 uM) treatment similarly inhibited short (4 hr) and long-term (24 hr) cell migration and cell invasion. PDGF-BB activation of PDGFRβ, PI3K, Akt and Erk1/2 was simultaneously inhibited by SUTENT treatment, while PTEN activity was promoted, without any affect on apoptosis. siRNA silencing of PDGFRβ similarly inhibited survival, migration and signaling and both siRNA and Imatinib or SUTENT treatment inhibited PDGF-BB-induced EGFR trans-activation. Inhibition of PDGFRβ in medulloblastoma cells by siRNA or drug treatment effectively blocked PDGFRβ signaling and EGFR transactivation and concomitantly inhibited cell migration and invasion. These results indicate that PDGFRβ tyrosine kinase activity is critical for survival and migration/invasion of medulloblastoma cells, in part by decreasing PTEN activity and transactivating EGFR, and thus may represent an important therapeutic target for this disease.